THE EFFECT OF JOB STRESS AND ORGANIZATIONAL CLIMATE ON TURNOVER INTENTION WITH JOB SATISFACTION AS A MEDIATION VARIABLE - Lukas, Amos; Goenawan, R. Djoko; Moeins, Anoesyirwan (Yayasan Pusat Cendekiawan Intelektual Nusantara, 2024)
This study explores the influence of work stress and organizational climate on turnover intention by considering the role of job satisfaction as a mediator. Through analysis of 135 respondents from several housing development companies in Pekanbaru City, using the Simple Random Sampling method, we found that work stress has a positive and significant influence on the desire to change jobs. Apart from that, job satisfaction has also been proven to mediate the relationship between job stress and turnover intention. The results also show that organizational climate has a negative and significant influence on turnover intention, however, job satisfaction also mediates the relationship between organizational climate and desire to change jobs. Proposed suggestions include expanding mental wellbeing support programs to deal with work stress, improving communication between management and employees to improve organizational climate, implementing balanced work policies to increase job satisfaction, and conducting interviews to identify key factors that drive turnover intention.